Multimedia fax-MIME interworking. - Patel, Sanjiv Purushottamdas. (University of Ottawa (Canada), 1994)
In this thesis, the architecture of an application-level Internet-fax gateway to facilitate multimedia messaging and to extend Internet services to the home or office is presented. We propose the use of the latest developments in the facsimile and Internet worlds, notably BFT support for Group3 protocols and MIME, for the exchange of multimedia messages (documents) between both environments as well as providing Internet e-mail, file transfer and Internet news services to fax users. Such services would be of most benefit to Internet novices and those users who do not have access to Internet via dialup/SLIP or Freenet facilities. The gateway services would allow a smooth transition into the widespread proliferation of multimedia communications. Implementation of such a gateway would make multimedia at home a very practical reality. A remote printer server, whose functionality is a subset of the proposed multimedia fax-Internet gateway was configured and setup at the MCRLab. This server became operational on February 3, 1994 and covers the local calling areas of the Ottawa/Hull region. This exercise gave us better insight into the practical aspects of the Internet Remote Printing Experiment. Further, a demo for inbound multimedia messaging was developed using the Binary File Transfer extensions to CCITT Group3 facsimile. This prototype serves as a proof of concept for the proposed gateway services.
Keywords: Engineering, Electronics and Electrical.